Comparison of the Effectiveness of Suffering Management Training and Emotion Efficacy Therapy on Life Suffering and Affective Capital in Individuals with Irritable Bowel Syndrome - Khaki, Saeideh; Golparvar, Mohsen; Yousefi, Zahra (Mental Health and Lifestyle Journal, 2025)
Patients with Irritable Bowel Syndrome (IBS) require not only medical treatment but also psychological interventions. Accordingly, this study aimed to compare the effectiveness of suffering management training and emotion efficacy therapy on life suffering and affective capital in patients with IBS. This research employed a quasi-experimental design with pretest, posttest, and follow-up phases along with a control group. The statistical population consisted of all IBS patients who referred to gastroenterology clinics in Isfahan during the winter of 2025. From this population, 60 patients were purposefully selected and assigned into three groups (each with 20 participants). The Perceived Suffering Scale (Schulz et al., 2010) and the affective Capital Questionnaire (Golparvar, 2016) were used to assess the dependent variables across the three time points. The two treatment groups each received 8 sessions of intervention lasting between 75 to 95 minutes, while the control group received no treatment. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc test via SPSS version 26. The results indicated that for both variables—life suffering and affective capital—there were significant differences between the suffering management training group, the emotion efficacy therapy group, and the control group (p < .05). Specifically, suffering management training was more effective than emotion efficacy therapy in reducing life suffering and enhancing affective capital. Given the effectiveness of suffering management training in alleviating life suffering and improving affective capital among IBS patients, it is recommended that this psychological intervention be implemented alongside medical treatments in clinical settings.